Sequential phosphorylation of the phosphoprotein of vesicular stomatitis virus by cellular and viral protein kinases is essential for transcription activation. - Barik, S (1992)
The phosphoprotein (P) and the large protein (L) constitute the RNA-dependent RNA polymerase of vesicular stomatitis virus (VSV). We show that phosphate-free P protein expressed in bacteria is transcriptionally inactive when reconstituted with L protein and viral N-RNA template free of cellular protein kinase. Phosphorylation of P protein by a cellular kinase(s) was essential for transcription as well as for further phosphorylation by an L-associated kinase, the two kinases acting in a sequential (cascade) manner. Phosphate groups introduced by cell kinase were stable, whereas those due to L kinase underwent a turnover which was coupled to ongoing transcription. We present a model for the phosphorylation pathway of P protein and propose that continued phosphorylation and dephosphorylation of P protein may represent a transcriptional regulatory (on-off) switch of nonsegmented negative-strand RNA viruses.